SOCIAL NORMS AND PUNISHMENT: A SOCIOLOGICAL APPROACH - Keltoum Berani (International Journal of Innovative Technologies in Social Science, 2025)
All societies require rules that guide the behaviour of individuals as members of the collective. Some rules are social norms (customs), while others are codified as formal laws (legal standards). Violating such rules is considered deviant behaviour. It elicits a social or legal reaction legitimised by customary belief or legal text, ranging from simple social condemnation to judicial punishment. What, then, is the relationship between social norms and legal sanctions? Suppose the law is regarded as a social value and a normative reference. How can this interrelation be explained through a sociological approach that considers both normative systems and legal rules as social phenomena created by the group in response to organisational needs and the preservation of social structure and cohesion?